(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
Emerging evidence indicates that older populations across Sub-Saharan Africa face a disproportionately high burden of unmet health and social care needs. Gaining a clearer understanding of these unmet needs is essential for informing the development of strategies, policies, and programmes that can strengthen service delivery, promote equity, and improve health and social outcomes among older adults. This study thus aimed to synthesise a range of existing evidence addressing the unmet health and social care needs of the aged in sub-Saharan Africa. Three electronic databases—PubMed, Springer Nature Link, and African Journals Online—were systematically searched. A comprehensive search strategy was developed using a combination of keywords, and a two-stage screening process was employed. A total of 31 studies met the inclusion criteria. The findings from these studies were synthesised narratively. The review identified a wide range of unmet health and social care needs among older adults in Sub-Saharan Africa. These included a high prevalence of non-communicable diseases, nutritional deficiencies, limitations in activities of daily living, social isolation, depression, and psychological distress. Many of these unmet needs were linked to broader social determinants of health and inequalities, such as financial hardship, poor living conditions, unhealthy lifestyle factors, societal beliefs about ageing and western medicine, geographical disparities, gender inequality, and weaknesses within the health system. Formal care was often regarded as a last resort. The findings indicate an urgent need for sensitisation and public awareness about the challenges associated with ageing, and how to ensure healthy ageing. This will help reduce the stigma and marginalisation of the elderly and also encourage the acceptance of Western medicine. Further research focusing on coordinated care models and the role of technology in enhancing service delivery is essential to inform policy and practice in the region.